Paclitaxel for treatment of advanced small cell lung cancer (SCLC): a retrospective study of 185 patients - Eiff, Damian von; Bozorgmehr, Farastuk; Chung, Inn; Bernhardt, Denise; Rieken, Stefan; Liersch, Stephan; Muley, Thomas; Kobinger, Sonja; Thomas, Michael; Christopoulos, Petros; Steins, Martin (Journal of thoracic disease, 2020)
Background: Etoposide-/platinum-based chemotherapy is the standard first-line treatment for extensive- disease small cell lung cancer (SCLC), but responses are short-lived and subsequent options limited. Here, we present our experience with paclitaxel in advanced treatment lines. - Methods: We retrospectively studied the clinical course of all paclitaxel-treated SCLC patients between 2005 and 2015 in our institution. Prognostic and predictive factors were analyzed by Kaplan-Meier and Cox regression analyses. - Results: A total of 185 patients [119 men, median age 65 years, median ECOG performance status (PS) 1] were identified. One hundred and sixty-eight patients had extensive disease (ED) at the time of paclitaxel therapy. Paclitaxel was mainly given as third- or fourth-line therapy (93%). The response rate (RR) was 17% and disease control rate (DCR) 28%. Patients reached a median progression-free survival (PFS) of 1.6 (95% CI: 1.4-1.8) months and median overall survival (OS) of 3.3 (95% CI: 2.8-3.9) months. Main toxicities were fatigue (25%) and polyneuropathy (17%). Dose reduction of ≥25% was associated with shorter PFS [1.9 (95% CI: 1.5-2.3) vs . 1.4 (95% CI: 1.3-1.5) months; P=0.004]. Further independent predictive factors for PFS were gender, age, and hepatic/brain metastases (P vs . 62%), as well as a comparable DCR (29% vs . 28%), which was associated with prolonged survival (4.5 vs . 3.2 months for refractory cases, P=0.034). - Conclusions: Paclitaxel has clinically relevant activity in heavily pretreated SCLC. While patients with good PS and no cerebral/hepatic metastases derive the greatest benefit, ECOG PS 2 per se should not be used as a criterion to exclude patients.